(untitled) (Filozofia Edukacji, 2023)
This article aims at introducing to the fundamental assumptions of an immanent ontology of teaching. The analysis departures from the reasons behind the project of an ontology of teaching. Next, the specificity of this project is addressed, through pointing to a difference between the possible investigation into the ontic of teaching, and giving the ontological account of teaching. Furthermore, the issue of the immanence is addressed in relation to the role of phenomenology in the attempt to speak out teaching from within. And finally, two main theses of immanent ontology of teaching are being analysed: there is educational love, and there is educational equality.